CIE L*a*b* Color Space Based Vegetation Indices Derived from Unmanned Aerial Vehicle Captured Images for Chlorophyll and Nitrogen Content Estimation of Tea (Camellia sinensis L. Kuntze) Leaves - Wahono Wahono; Didik Indradewa; Bambang Hendro Sunarminto; Eko Haryono; Djoko Prajitno (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2019)
A lot of digital image techniques to assess crop agronomic character have been developed. Most of those techniques are based on non-visible light equiped cameras, such as infared wavelengths. This research was aimed to examine the use of commercial digital camera with sensor range in visible light spectrum using CIE L*a*b* color space to estimate chlorophyll and nitrogen content of tea leaf. Data was collected from an experiment of nitrogen dossage levels on 3 years after prunning tea crops. The result shows that Lb* Difference Simple Index (LI), a*b* Difference Simple Index (AI), and a* Vegetation Index (VIA) can be used to estimate tea leaf chlorophyll and nitrogen content. The relationship between VIA and tea leaf nitrogen content was defined on linear equation y = 1.8382x2 - 0.3099x + 3.0658 with determinant coefficient R² = 0.71.